How to Improve Problem Solving Ability in Learning Physics: A Systematic Review - Faiz Mudhofir; Edy Cahyono; Sigit Saptono; Sulhadi Sulhadi (International Conference on Science, Education, and Technology, 2022)
Abstrak. Development of Problem-solving skills is needed in physics to master concepts. This goal can be achieved through the implementation of the right steps. The purpose of this research is to describe models, strategies, media, and instruments that can be used to develop problem-solving skills. Learning models that can be applied include PBL, PIL, Inquiry, IBMR, PO2E2W, Discovery Learning, PjBL, Virtual Laboratory, CPSL, and CTL learning models. Learning strategies can be in the form of peer instruction, scaffolding, Polya strategies, Heller, Keith, and Enderson strategies, knowledge planning strategies, Rosengrant strategies, and visualization of the imaginary world. Various supporting media can be in the form of computing media, the development of teaching materials, mobile applications, and games. The instruments used for assessment and questionnaires.